BOUNDARIES OF TRUST AND TRANSGRESSION: STUDYING THE CIRCULATION OF OBSCENE CONTENTS WITHIN ITALIAN PRIVATE GROUP CHATS - Boccia Artieri, Giovanni; Zurovac, Elisabetta; Brilli, Stefano (AoIR Selected Papers of Internet Research, 2019)
Within the contemporary social media sphere we witnessed an exploitation of visible and permanent contents shared by users for platforms’ marketing purposes (i.e. selling data to advertisers) and to enable platforms to provide tailored experiences. This, along with data breaches scandals, triggered concerns about privacy and the dangers of mass surveillance, and lead developers to provide Instant Messaging applications with greater security. However, the existence of this kind of ‘safe spaces’ in which users privacy is not menaced, has also raised the attention on the sharing of transgressive, obscene or offensive contents that eludes public scrutiny. While the mainstreaming of such contents in non-public digital spaces is often cited as one of the hallmarks of the “dark side of the web”, the research on this topic is still lacking as this phenomenon is observable mostly at an interactional level, and not at the mass media system level. Our study provides an analysis of users’ meaning-making and boundary maintenance activities regarding violent/pornographic contents in group chats (WhatsApp and Telegram), that combines participant observation and in-depth interviews with active participants of such groups. We expect that the results of this research will improve the understanding of 1) the role of messaging apps affordances in shaping the circulation of extreme contents, 2) group trust dynamics, 3) the impact of a common semantics of the obscene on the cultivated semantics of public sphere, 4) methodological difficulties in researching online spaces unreachable by web scraping approaches.